Uji Aktivitas Antibakteri Ekstrak Kasar Bawang Putih (Allium sativum ) terhadap Bakteri Shigella dysenteriae yang Resisten terhadap Ampisilin - Arimaswati Arimaswati; Yessy Toding Mendaun; Yenti Purnamasari (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACT Background : Gastrointestinal infections, especially caused by Shigella dysenteriae bacteria is still a health issue in Indonesia. The number of ampicillin resistance to S. dysenteriae has been widely reported. Garlic (Allium sativum) is a traditional medicine that efficacy as an antibacterial. Garlic contains an organosulfur compound  Allicin. Research Purpose: This study aimed to determine the antibacterial activity of garlic rule extract on the growth of S. dysenteriae bacteria that are resistant to ampicillin. Research Methods: This study used the experimental with post test only control group design. The antibacterial activity test was determined based on the diameter of clear zone formed. Test  were performed  on garlic filtrate, ciprofloxacin as a positive control and aquades as a negative control. Each treatment was performed three times. Research Result: This research showed that rule extract of garlic (A. sativum)  had a clear zone against S. dysenteriae that was resistant to ampicillin. Conclusion: The conclusion of this research was that rule extract of garlic (A. sativum) had an antibacterial activity against S. dysenteriae which resistant to ampicillin.  Keywords : Antibacterial activity, Garlic (A. sativum), S. dysenteriae